A BUSINESS GAME FOR THE INTRODUCTORY COURSE IN ACCOUNTING. - Gray, Jack; Willingham, John; Johnston, Kinneth (The Accounting Review, 1963)
This article presents a business game that was developed for use in an introductory accounting course. Most such games are much too complex for classroom use in the introductory course. This game is designed to: 1) Require the student to think about a number of significant accounting problems and economic concepts. 2) Motivate an extremely high proportion of students to lean how accounting is used in decision-making. 3) Be simple enough that it can be used in the classroom without any calculating equipment.